German training revisited: An appraisal of corporatist governance - Lange, Thomas (Emerald, 2012)
Purpose: The aim of this paper is to re‐examine the unique political economy of Germany's dual apprenticeship training model and its underlying philosophy of corporatist governance. It responds to recent arguments suggesting that Germany's collectivist skill regime is under threat, increasingly giving way to the introduction of “segmentalism”. Design/methodology/approach: The paper reviews the political roots of a training system, which is moulded and shaped by corporatist interventions and neocorporatist compromises. It applies “public choice” theory to different interest groups in Germany's training market. The focus is on the German apprenticeship system as a social and political institution. The paper is positioned in the tradition of inductive enquiry, which draws on an interpretive framework and is informed by reference to a cross‐section of the extant literature in several social science disciplines. Findings: The German training system is the product of a wider post‐war consensus, yet continues to face social inequality concerns, which culminate in significant economic and societal costs. Despite modernisation attempts, the German apprenticeship is the outcome of a complicated political process, linked to its historical origins, which allows for a considerable degree of self‐interest alongside its corporatist roots and values. Amongst Germany's social partners, heterogeneous self‐interests and corporatism can co‐exist, thus identifying an alternative model to collectivism and segmentalism.Originality/value: The paper rejects recent suggestions that the German system moves towards a model of “segmentalism”. Instead, it interprets the German system as an example for a specific socio‐political constellation where significant self‐interests and corporatist rules can co‐exist. Against this background, it demonstrates that continuing demands to copy the German apprenticeship model – if thought desirable – are unlikely to be successful unless this tangled web of political processes and interests is fully understood.